2020
DOI: 10.1038/s41467-020-16430-2
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic and electronic phase transitions probed by nanomechanical resonators

Abstract: The reduced dimensionality of two-dimensional (2D) materials results in characteristic types of magnetically and electronically ordered phases. However, only few methods are available to study this order, in particular in ultrathin insulating antiferromagnets that couple weakly to magnetic and electronic probes. Here, we demonstrate that phase transitions in thin membranes of 2D antiferromagnetic FePS3, MnPS3 and NiPS3 can be probed mechanically via the temperature-dependent resonance frequency and quality fac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
125
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 92 publications
(134 citation statements)
references
References 31 publications
7
125
1
1
Order By: Relevance
“…[ 111 ] Recent work has demonstrated that the antiferromagnetic phase transition in 2D FePS 3 flakes can be probed by nanomechanical resonators and revealed that specific heat plays a mediated role between mechanical motion and antiferromagnetic order (Figure 6d,e). [ 22 ] Moreover, the strong dependence between the Neel temperature and electrostatically induced strain in 2D FePS 3 flakes has also been confirmed. [ 22 ] Due to the existence of close coupling between mechanical motion and magnetic sequence, nanomechanical resonator is a promising tool for characterizing the phase transition of 2D magnetic materials.…”
Section: Novel Properties Of 2d Lpcsmentioning
confidence: 87%
See 2 more Smart Citations
“…[ 111 ] Recent work has demonstrated that the antiferromagnetic phase transition in 2D FePS 3 flakes can be probed by nanomechanical resonators and revealed that specific heat plays a mediated role between mechanical motion and antiferromagnetic order (Figure 6d,e). [ 22 ] Moreover, the strong dependence between the Neel temperature and electrostatically induced strain in 2D FePS 3 flakes has also been confirmed. [ 22 ] Due to the existence of close coupling between mechanical motion and magnetic sequence, nanomechanical resonator is a promising tool for characterizing the phase transition of 2D magnetic materials.…”
Section: Novel Properties Of 2d Lpcsmentioning
confidence: 87%
“…[ 22 ] Moreover, the strong dependence between the Neel temperature and electrostatically induced strain in 2D FePS 3 flakes has also been confirmed. [ 22 ] Due to the existence of close coupling between mechanical motion and magnetic sequence, nanomechanical resonator is a promising tool for characterizing the phase transition of 2D magnetic materials.…”
Section: Novel Properties Of 2d Lpcsmentioning
confidence: 90%
See 1 more Smart Citation
“…More broadly, light absorption and emission could be controlled electro-mechanically in nanoresonators made from custom-designed van der Waals heterostructures 60 . Going one step further, with the emergence of 2D materials featuring robust magnetic order and topological phases 61 , that can be probed using optical spectroscopy, we foresee new possibilities to explore and harness phase transitions using nanomechanical resonators based on 2D materials 62 , 63 .…”
Section: Discussionmentioning
confidence: 99%
“…This intimate relationship between magnetic order and anisotropy in 2D motivates the ongoing search for efficient pathways to manipulate the magnetic anisotropy in such systems. Since the magnetic anisotropy in most materials is determined by the coupling of electronic orbitals and spins, stabilizing and controlling 2D magnetism are actively pursued through the manipulation of orbital degrees of freedom, using, for example, mechanical strain (6)(7)(8) and electrostatic gating (9,10). However, a large anisotropy is normally associated with an unquenched orbital moment, which is limited to specific oxidation states and to low-symmetry crystal environments, most notably for rare-earth ions (11).…”
Section: Introductionmentioning
confidence: 99%